2014
DOI: 10.1017/s1474747214000377
|View full text |Cite
|
Sign up to set email alerts
|

Investment in financial literacy, social security, and portfolio choice

Abstract: We present an intertemporal portfolio choice model where individuals invest in financial literacy, save, allocate their wealth between a safe and a risky asset, and receive a pension when they retire. Financial literacy affects the excess return from and cost of stock-market participation. Investors simultaneously choose how much to save, their portfolio allocation, and the optimal investment in financial literacy. The model implies that one should observe a positive correlation between stock-market participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(66 citation statements)
references
References 63 publications
3
62
0
1
Order By: Relevance
“…Moreover, it is believed that financial literacy plays an important role because it has been related to saving behaviour and portfolio choice. According to Jappelli & Padula, (2015), there is a positive association between financial literacy accumulated early in life and the individual's wealth and portfolio allocations in later life. Generally, there may be an impact of financial literacy on financial decision-making (Disney et al, 2015), because it is necessary to learn about finance in order to make the right financial decisions (Calcagno & Monticone, 2015) and invest the most effectively (Capuano & Ramsay, 2011), which helps accumulate their wealth (Jappelli & Padula, 2013;van Rooij et al, 2011;Lusardi & Mitchell, 2011).…”
Section: Actual and Perceived Financial Literacy And Financial Behaviourmentioning
confidence: 99%
“…Moreover, it is believed that financial literacy plays an important role because it has been related to saving behaviour and portfolio choice. According to Jappelli & Padula, (2015), there is a positive association between financial literacy accumulated early in life and the individual's wealth and portfolio allocations in later life. Generally, there may be an impact of financial literacy on financial decision-making (Disney et al, 2015), because it is necessary to learn about finance in order to make the right financial decisions (Calcagno & Monticone, 2015) and invest the most effectively (Capuano & Ramsay, 2011), which helps accumulate their wealth (Jappelli & Padula, 2013;van Rooij et al, 2011;Lusardi & Mitchell, 2011).…”
Section: Actual and Perceived Financial Literacy And Financial Behaviourmentioning
confidence: 99%
“…Monticone (2010) adapts this model to the context of financial literacy and wealth accumulation. Dynamic human capital models of financial literacy accumulation are set up by Delavande et al (2008), Jappelli and Padula (2013), and . In these frameworks, financial literacy enables the realisation of higher returns, but requires time and money investments.…”
Section: Financial Literacy and Financial Decision-makingmentioning
confidence: 99%
“…Thus, individuals will invest in financial literacy until their marginal benefits of acquiring financial knowledge are equal to their marginal costs. While Delevande et al (2008) and Jappelli and Padula (2013) focus on two period frameworks, model a full life-cycle model with endogenous financial 7 literacy. In their model, the need to smooth consumption at retirement simultaneously drives the savings decision (wealth accumulation) and investment in financial knowledge.…”
Section: Financial Literacy and Financial Decision-makingmentioning
confidence: 99%
See 1 more Smart Citation
“…The study also found that households with financial literacy have fair investment outcomes while individuals who have low financial literacy and who believe in their own decision making, face losses. Jappelli and Padula (2014) found that financial literacy has positive correlation with investors' wealth and portfolio diversification and suggested that financial literacy allows investor better investment opportunities. Dimmock, Kouwenberg, Mitchell, and Peijnenburg (2016) pointed out that financial literacy improves the financial decisions of investor and reduces the ambiguity aversion.…”
Section: Literature Review Financial Literacy and Portfolio Diversifimentioning
confidence: 99%